Mechanics for engineers : - Beer, Ferdinand Pierre (McGraw-Hill, 1987)
The first book published in the Beer and Johnston Series, Mechanics for Engineers: Dynamics is a scalar-based introductory dynamics text, ideally suited for engineering technology programs, providing first-rate treatment of rigid bodies without vector mechanics. This new edition provides an extensive selection of new problems and end-of-chapter summaries. The text brings the careful presentation of content, unmatched levels of accuracy, and attention to detail that have made Beer and Johnston texts the standard for excellence in engineering mechanics education.